Darwin and the island - Fox, J; Fox, Justin Daniel (1995)
﻿ This thesis examines the fictional island and assesses the impact of Darwinism on the genre. I show how islands have been a recurring feature in European literature, fictional spaces where authors create a microcosm in which they satirise, criticise or hold up a mirror to their own society. I argue that traditonal Utopian islands are static realms and that through the introduction of evolution (Darwin and Wallace made their most important discoveries regarding the mechanism of evolution on islands) fictional islands of the last century and a half have been radically transformed. The elements of chance, change, random mutation, natural and sexual selection, survival of the fittest as well as the knowledge of an animal heritage have changed the castaway experience, making it a far more anti-utopian one. The publication of The Origin of Species forced a reappraisal of all areas of knowledge and I show how, in the laboratory of the fictional island, authors examine the implications of Darwin's theory. Closely related issues are also taken into account, such as degeneration, the Second Law of Thermodynamics, developments in evolutionary anthropology, psychoanalysis and the coming of modern scientific method. I conduct a close reading of H. G. Wells' The Island of Doctor Moreau in which I consider the phenomenon of the mad scientist (in this case a modern, distinctly Darwinian scientist). Using some of Wells' scientific articles as a starting point, I show how the doctor tries to replicate a speeded up version of evolution in his island laboratory. Wells was a student of T. H. Huxley and the chapter examines the situation on the island in relation to Huxley's famous essay, "Evolution and Ethics", in which he argues that the "cosmic process" must be fought with an "ethical process". Wells called the novel a "theological grotesque" and I show how the novelist parodies orthodox Christianity and creates a protagonist who is a perverted evolutionary "god". Much of the remainder of the chapter is a detailed examination of degeneration in which I describe how the beast begins to resurface in Moreau's half-human creations as well as in the human protagonists (graphically evidenced in a "return" to cannibalism). A chapter on Joseph Conrad considers the pessimistic intellectual, philosophical and metaphysical forces that affect the novelist and his protagonist. First I show how the fin de siècle mood, in conjunction with the popular contemporary philosophies of Schopenhauer and Nietzsche (perceived in the light of Darwinian science) colour the cerebral landscape of Victory. The main thrust of this chapter concerns the issues of degeneration and devolution and in this respect I examine contemporary fears concerning cannibalism, thermodynamics, atavism and the anarchy resulting from a corrosion within society. I show further how the issue of sexuality (with relation to such issues as miscegenation, heredity and perversion) bears directly upon the idea of degeneracy. Finally the chapter considers the case of the imperial subject, the other "races" represented on Samburan. Here I am particularly interested in the anthropological application of Darwinism: far from being degenerate or inferior, Conrad depicts the racial other as having the "biological" advantage. By the time William Golding wrote Lord of the Flies, evolutionary elements were coming to novelists diluted in many different areas of enquiry. I discuss how Golding's knowledge of (evolutionary) anthropology and archaeology create a blueprint for the regression of English schoolboys to the level of "savages" and metaphorically to the level of early hominids and even animals. I show how the evil they try to externalise arises from within and is a part of their "animal" heritage. The chapter traces the path of their regression looking at aspects of their microcosmic society and religion. I also consider the situation of Golding's boys with relation to Freud's Totem and Taboo and his theories of child sexuality. Finally Golding's attempt to chart an existential and spiritual course through the waters of evolutionary determinism is discussed. In my concluding chapter I account for the "demise" of the Darwinian island showing how new issues are dominating the genre and in a close reading of Marianne Wiggins' John Dollar and J. M. Coetzee's Foe I examine how and why the postmodern and poststructuralist island fails to live up to the exigencies of the genre.